Greenhouse production of baby leaf vegetables using rainbow trout wastewater in a high-tech vertical decoupled aquaponic system - Chatzigeorgiou, Ioanna; Ravani, Maria; Papadopoulos, Dimitrios K.; Kelesidis, George; Giantsis, Ioannis A.; Tsaballa, Aphrodite; Koukounaras, Athanasios; Ntinas, Georgios K. (Frontiers in Horticulture, 2024)
Aquaponics is an integrated food production system, that links recirculating aquaculture with hydroponics, leading to higher water use efficiency than conventional food production systems, while also saving fertilizers. In the present study baby lettuce and baby rocket plants cultivated hydroponically in a deep water culture system using rainbow trout’s wastewater, were evaluated as part of a vertical decoupled aquaponic system. More specifically, three different nutrient solutions were supplied, using (a) fish wastewater only (designated as Fish), (b) fishwater enriched with synthetic fertilizers (Mix), and (c) a typical (Hoagland) nutrient solution as the control. Both lettuce and rocket plants were monitored on those nutrient solutions and in two different substrates, peat, and perlite, as an organic and an inert one. The purpose of this study was to assess a vertical decoupled aquaponic system, regarding resources use efficiency, such as water, land, and energy, while evaluating plants’ cultivation in the different treatments, in terms of yield, growth, nitrate concentration on leaf tissue and foliar analysis. Photosynthetic rate and leaf color indexes were also considered regarding plants’ evaluation. Mix-Peat treatment was the most efficient growing combination regarding land and water use efficiency, having approximately 7% better land use efficiency, while using 38% less water and 10% less fertilizers than Hoagland-Peat. Lettuce plants had the highest yield in Mix-Peat treatment as well, at 2497 g m-2, which was approximately 6% higher than Hoagland-Peat, while not being inferior in quality characteristics. On the other hand, rocket’s yield was significantly higher in the Hoagland-Peat treatment, being 18% higher than Mix-Peat and 30% higher than Fish-Peat. Overall, our study confirmed that aquaponic systems may lead to higher water use efficiency and saving in fertilizers, without undermining lettuce’s yield and quality, while the vertical arrangement developed within the scope of this study, can increase land use efficiency of the system.